1998
DOI: 10.1063/1.869617
|View full text |Cite
|
Sign up to set email alerts
|

Convection velocities in a turbulent boundary layer

Abstract: The convection velocities of ejections, sweeps, and shear layers have been studied in a turbulent boundary layer at Reθ=1409 by means of two-point correlations. Except in the buffer layer, where the convection velocities are reasonably constant, considerable variations in Uc are observed, both with respect to the distance from the wall and the scale of the event. The largest-scale motions (of the order of the boundary layer thickness) are convected at velocities close to the local mean. However, the velocities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
74
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 20 publications
23
74
0
Order By: Relevance
“…The angle γ was measured when a streak reached the maximum inclination from the mean flow direction. The maximum angle of inclination of about 30 • detected in our visualizations compares well with an estimate given by the vector of the convection velocity U c at this height (U + c ≈ 10, as shown by Krogstad et al [25]) and the vector of the peak spanwise velocity of the Stokes layer, also at y + = 5 and for T + = 67 and W + m = 17. The maximum angle can then be estimated as follows:…”
Section: Jot 5 (2004) 024supporting
confidence: 70%
“…The angle γ was measured when a streak reached the maximum inclination from the mean flow direction. The maximum angle of inclination of about 30 • detected in our visualizations compares well with an estimate given by the vector of the convection velocity U c at this height (U + c ≈ 10, as shown by Krogstad et al [25]) and the vector of the peak spanwise velocity of the Stokes layer, also at y + = 5 and for T + = 67 and W + m = 17. The maximum angle can then be estimated as follows:…”
Section: Jot 5 (2004) 024supporting
confidence: 70%
“…Kim & Hussain (1993) also found that the phase velocity of v was relatively insensitive to λ x and increased weakly with λ z , but their computational domain was too small to show the sharp growth of c for long and wide wavelengths. Krogstad, Kaspersen & Rimestad (1998) investigated a laboratory boundary layer at Re τ ≈ 600, and found an increase of the advection velocities at roughly the same values as those in figure 7.…”
Section: Dynamicsmentioning
confidence: 72%
“…18 To confirm that such fluctuations of U R do not affect our study of v 2 R , we calculate their correlation…”
Section: Fig 3 (Color) Probability Distribution Of Vmentioning
confidence: 99%